Environmental, Social and Governance (ESG) reporting – through the Chinese ‘lenses’ - Rowe, Anna (Wiley-Blackwell, 2016)
This engagement-based paper in understanding Environmental, Social and Governance (ESG) reporting by enterprises is aimed at exploring the complexity and emerging phenomenon within the Chinese context. As one of the few initiatives to explore senior managers’ perceptions toward ESG in China grounded empirically in utilizing qualitative methodology, this study seeks to bridge the gap of existing ESG research, which is dominated by quantitative research and studies in developed ‘western’ countries. It adds to the sparse literature pertaining to rich cultural ‘emic’ data in the field. In addressing this, semi-structured in-depth interviews were conducted with senior managers from 21 companies in various industries in China. An inquiry paradigm utilising constructivist ontology and interpretivist epistemology was required in understanding the normative assumptions underpinning ESG reporting in China through the lenses of the participants. This paper is part of a larger field study on ESG in China. This paper extends the utilisation of a variety of social system-based theoretical concepts such as stakeholder theory, legitimacy theory and institutional theory that have been approached by various accounting researchers. This study provides emerging themes that appear to highlight five main motivating drivers and six major barriers that impede ESG reporting in China as perceived by the senior managers. What sets it apart contextually from most research is the salient low-key Chinese culture that emerged as a barrier to implementation of ESG reporting. This study is significant to ESG practice in China with both theoretical and practical implications. It contributes to the body of knowledge in the use of systems-oriented theories. Its findings are helpful in refining recommendations to aid regulators and companies in identifying strategies likely to yield improved ESG reporting for economies with similar context to China.